Traits of the host trees, not community diversity, drive epiphytes abundance in tropical seasonal forests - Schievenin, Dimitrio Fernandes [UNESP]; Santos, Camila Alonso; de Lima, Karina; de Melo, Antônio Carlos Galvão; Engel, Vera Lex [UNESP]; Durigan, Giselda [UNESP] (FapUNIFESP (SciELO), 2024)
Epiphytes are considered indicators of forest ecological integrity, but the factors that explain their abundance are still not well understood. We here evaluated tree colonization by epiphytes in old-growth monospecific reforestation stands of Astronium urundeuva (M.Allemão) Engl. (Anacardiaceae) and Eucalyptus saligna Sm. (Myrtaceae), in comparison to a neighbor seasonal tropical forest fragment under similar environmental conditions. In each forest type, we identified and measured all trees (planted and colonizers) from 5-cm stem diameter in five 200 m² plots and quantified all vascular epiphytes per tree. Tree species were categorized by bark roughness, canopy deciduousness and growth rate. The abundance of epiphytes and the frequency of host trees were higher in the A. urundeuva plantation than in the native forest, with the E. saligna stand in an intermediate position. Also, we found that host traits influenced the abundance of epiphytes in their trunks. Host trees had average stem perimeter and height both higher than non-hosts, which indicates that colonization is more likely to occur in older trees. The average abundance of epiphytes per tree was higher in species with rough bark, but no relationship was found with canopy deciduousness or tree growth rate. We evidenced, therefore, that forest plantations, even if monospecific, can provide habitat for epiphytes. However, at community level, colonization success, either in native or restored forest, depends on the relative abundance of species whose bark type favors epiphytes establishment.
Atributos das árvores hospedeiras, e não a diversidade da comunidade, conduzem a abundância de epífitas em florestas tropicais sazonais
Keywords: Epiphytism; Forest Restoration; Host Preference; Non-Tree Life Forms; Tropical Seasonal Forest